Ti, ti, ti na história: uma ferramenta midiática para o ensino de História - SILVA, Márcia Nascimento da (2018)
The work seeks to present the Facebook page Ti, Ti, Ti in History, as a technological tool capable of facilitating the teaching-learning process of the History discipline, paying attention to the specifics of the historian's work, that in this new moment of the search for construction of historical knowledge, approaches new approaches and resources for the classroom as an alternative to motivate students to take an interest in history classes. It is clear that there is no room left for the classroom that used to be students, teachers, chalkboard, tables and chairs. The teacher, as agent of transmission of knowledge, and aiming at improving the teaching of History in the country, needs to be attentive to new alternatives to complement teaching. Technology is one of them. It is necessary that school and teacher recognize the great importance that technology has in our lives, after all, there is nothing that currently attracts the attention of children and young people more than technology. We are no longer in time to ignore or avoid using it in the classroom. It's there, everywhere, all the time.